Digital content as a didactic strategy for the development of economic and financial knowledge in senior education students - Núñez-Rueda, Silvia Nathalia; Vargas-Daza, María del Pilar; Palacio-García, Luis Alejandro (Universidad Pedagógica y Tecnológica de Colombia, 2022)
This article presents the design process of a series of digital content (video game and editable primers) for the formation of economic and financial knowledge in high school students in Santander (Colombia). The design of the materials was carried out based on the results obtained with the implementation of the Design-Based Research methodology. From a sample of 107 high school students who participated in the testing phase, it is concluded that the digital content designed is a didactic resource that favors the learning of economic and financial concepts. This is because they encourage the practice of argumentative skills and allow the expression of their opinions on situations of daily life that are affected by bad financial decisions. In addition, they are contents that students recognize as necessary in their learning processes and as fundamental elements that allow them to learn in a better way.